Bioactive Material with Microorganisms can Enhance the Micronutrients Solubilization and Sulfate Availability from Low Reactive Sources: Insight for Application as Coating Fertilizer Granules - Majaron, Vinícius F.; da Silva, Marisa Gomes; Bortoletto-Santos, Ricardo [UNESP]; Klaic, Rodrigo; Ribeiro, Sidney J. L. [UNESP]; Polito, Wagner L.; Bevilaqua, Denise [UNESP]; Farinas, Cristiane S.; Ribeiro, Caue (Springer Nature, 2022)
Fertilization is essential to provide suitable conditions for plant development and crop productivity, but the environmental cost of fertilizers is a drawback for achieving a sustainable agriculture. A potential alternative is the use of unprocessed (raw) nutrient sources such as elemental sulfur (S0) and mineral oxides (ZnO, MnO, CuO) as fertilizers. However, these low reactive sources are not readily available to plants. Here, we developed a bioactive coating material containing microorganisms that allowed different nutrients to be made available from unprocessed nutrient sources. For that, the coating material composed of maize starch, elemental sulfur (S0), mineral oxides (ZnO, MnO, CuO), and a microbial source (Aspergillus niger or Acidithiobacillus thiooxidans) was applied on monoammonium phosphate (MAP) granules, as a model fertilizer. Our results revealed that the bioactive coating did not affect the phosphorus (P) release, since it did not impose a physical barrier. However, the acidifying capacity of both microorganisms significantly enhanced the oxide solubilization and elemental sulfur oxidation. The presence of Aspergillus niger or Acidithiobacillus thiooxidans promoted local acidification, achieving sulfate release of up to 76.4 and 83.8% in 42 days of soil incubation. Furthermore, the bioactive coating material with Aspergillus niger reached Cu, Zn and Mn solubilization up to 10.9, 14.6 and 34.3% in 42 days of soil incubation. This phenomenon suggested that the organic acids produced by Aspergillus niger chelate the cations, reducing precipitation and, therefore, increasing their solubilization. This innovative system can effectively supply nutrients to plants using cheap and low reactivity nutrient sources with the advantage that it can be co-applied on currently used fertilizer granules in a single delivery, making easier the adoption by producers. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Acidithiobacillus thiooxidans; Aspergillus niger; Fertilizer; Micronutrients; Starch